2016
DOI: 10.1038/ncomms12201
|View full text |Cite
|
Sign up to set email alerts
|

Observation of exceptional points in reconfigurable non-Hermitian vector-field holographic lattices

Abstract: Recently, synthetic optical materials represented via non-Hermitian Hamiltonians have attracted significant attention because of their nonorthogonal eigensystems, enabling unidirectionality, nonreciprocity and unconventional beam dynamics. Such systems demand carefully configured complex optical potentials to create skewed vector spaces with a desired metric distortion. In this paper, we report optically generated non-Hermitian photonic lattices with versatile control of real and imaginary sub-lattices. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 37 publications
(56 reference statements)
0
65
0
Order By: Relevance
“…The observable signatures of hybridization, level repulsion and line width evolution, are actually related to the presence of an exceptional point (EP) in the eigenspectrum -a branch point where the eigenmodes and eigenvectors coalesce [123]. EPs plays an important role in many physical systems [124][125][126][127][128][129][130][131][132] and, the mathematical origin of the magnon-photon EP can be easily understood by examining the hybridized dispersion. If the damping and coupling strength parameters are allowed to vary it is possible that the square root argument will become zero, and therefore the eigenmodes will become degenerate.…”
Section: Exceptional Points and Hybridizationmentioning
confidence: 99%
“…The observable signatures of hybridization, level repulsion and line width evolution, are actually related to the presence of an exceptional point (EP) in the eigenspectrum -a branch point where the eigenmodes and eigenvectors coalesce [123]. EPs plays an important role in many physical systems [124][125][126][127][128][129][130][131][132] and, the mathematical origin of the magnon-photon EP can be easily understood by examining the hybridized dispersion. If the damping and coupling strength parameters are allowed to vary it is possible that the square root argument will become zero, and therefore the eigenmodes will become degenerate.…”
Section: Exceptional Points and Hybridizationmentioning
confidence: 99%
“…When gain and loss are added to the phase modulation in a PT-symmetric fashion within the time window, unidirectional invisibility occurs at EPs. Hahn et al first observed totally asymmetric diffraction in a PTsymmetric photonic lattice at EPs using vector-field holographic interference of two elliptically polarized pump beams on azobenzene-doped polymer thin films [47].…”
Section: Unidirectional Reflectionless Propagation In Pt-symmetric Symentioning
confidence: 99%
“…Both the real and imaginary parts of the eigenvalues coalesce at this point. The EPs have been observed in many photonic systems, such as optical microcavities [29,30], coupled optical waveguides [31][32][33], photonic crystal slabs [34][35][36][37] and unidirectionally coupled resonators [38,39]. Many novel properties are also found at or near the EPs, such as loss-induced suppression and revival of lasing [40][41][42], unidirectional transmission or reflection [43][44][45][46][47][48], topological chirality [49][50][51] and laser mode selectivity [52][53][54].…”
mentioning
confidence: 99%